2018
DOI: 10.1158/0008-5472.can-17-1987
|View full text |Cite
|
Sign up to set email alerts
|

Germinal Centers Determine the Prognostic Relevance of Tertiary Lymphoid Structures and Are Impaired by Corticosteroids in Lung Squamous Cell Carcinoma

Abstract: In solid tumors, the presence of lymph node-like structures called tertiary lymphoid structures (TLS) is associated with improved patient survival. However, little is known about how TLS develop in cancer, how their function affects survival, and whether they are affected by cancer therapy. In this study, we used multispectral microscopy, quantitative pathology, and gene expression profiling to analyze TLS formation in human lung squamous cell carcinoma (LSCC) and in an experimental model of lung TLS induction… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

22
287
1
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 299 publications
(333 citation statements)
references
References 54 publications
22
287
1
1
Order By: Relevance
“…It was further shown that lung squamous cell carcinoma patients have less germinal centers in their TLS if they received cisplatin-based neoadjuvant chemotherapy, but the chemotherapy was co-administered with corticosteroids that could have a direct inhibitor effect on germinal center maturation. 30 To our knowledge, our observation is the first description of chemotherapy-induced TLS formation with paired prechemotherapy biopsies as a control, indicating that chemotherapy induces a peculiar immune response. This could involve the socalled immunogenic cell death (ICD), a class of controlled cell death processes that produce damage-associated molecular patterns which can act as adjuvants for initiating the immune response via the recruitment and activation of dendritic cells.…”
Section: Discussionmentioning
confidence: 60%
See 1 more Smart Citation
“…It was further shown that lung squamous cell carcinoma patients have less germinal centers in their TLS if they received cisplatin-based neoadjuvant chemotherapy, but the chemotherapy was co-administered with corticosteroids that could have a direct inhibitor effect on germinal center maturation. 30 To our knowledge, our observation is the first description of chemotherapy-induced TLS formation with paired prechemotherapy biopsies as a control, indicating that chemotherapy induces a peculiar immune response. This could involve the socalled immunogenic cell death (ICD), a class of controlled cell death processes that produce damage-associated molecular patterns which can act as adjuvants for initiating the immune response via the recruitment and activation of dendritic cells.…”
Section: Discussionmentioning
confidence: 60%
“…26 While it has been known for a long time that chemotherapy can increase the number of tumor -infiltrating lymphocytes in different neoplasms such as breast 27 or ovarian cancer, 28 the effect of neoadjuvant chemotherapy on TLS is poorly documented. In different types of lung cancers, 29,30 intratumor TLS have been described both in the presence and the absence of chemotherapy. It was further shown that lung squamous cell carcinoma patients have less germinal centers in their TLS if they received cisplatin-based neoadjuvant chemotherapy, but the chemotherapy was co-administered with corticosteroids that could have a direct inhibitor effect on germinal center maturation.…”
Section: Discussionmentioning
confidence: 99%
“…Since there is no established TLS classification, previous studies adopted their own classifications. 12,25,26 One previous report of ovarian cancer classified lymphoid aggregates into four types based on size, cellular composition, and degree of GC organization. 25 The authors examined the associations between the four types and tumor infiltrating lymphocytes (TILs) and plasma cell densities, whereas they did not mention the relationships of the four types to clinical outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…51 In contrast, caution is advised when administrating corticosteroids to manage chemotherapy side effects, as it could decrease the density of TLS in patients with lung squamous cell carcinomas. 52 These findings are valuable to help us develop immunotherapies that specifically enables the formation of TLS to improve the prognosis of patients with GIST.…”
Section: Discussionmentioning
confidence: 98%